223k views
6 votes
(282-14*3*6)/(6) -(21-18)

User Rakhil
by
4.4k points

2 Answers

5 votes

Answer:


27

Explanation:

1) Simplify 14 × 3 to 42.


282 - 42 * 6 - (21 - 18)

2) Simplify 21 - 18 to 3.


282 - 42 * 6 - 3

3)Simplify 42 × 6 to 252.


282 - 252 - 3

4) Simplify 282 - 252 to 30.


30 - 3

5) Simplify.


27

Therefor, the answer is 27.

User JKHA
by
5.1k points
7 votes

Answer:

2

Explanation:

( 282 - 14 ⋅ 3 ⋅ 6 ) / ( 6 ) - ( 21 - 18 )

= 30/( 6 ) - ( 21 - 18 )

= 30/( 6 ) - 3


=(30)/(6) -3

= 2

User Fakataha
by
4.8k points